Holla Churros / Muhammad Izzat Amar Azmi... [et al.] - Azmi, Muhammad Izzat Amar; Ismail, Abdul Halim; Zakaria, Nur Amni; Suhaimi, Muhammad Alif Izzuddin; Rusli, Nur Azlin; Mohamad Kamarudin, Hairil Azfar (2015)
HOLA Churros is a food company that sells churros with different types of topping and dip. Some of the available topping and dips are chocolate, whipped cream, caramel and fruit toppings.